Microbiology for dummies - Stearns, Jennifer C.; Kaiser, Julie; Surette, Michael G. (Hoboken : John Wiley & Sons, 2015)
Does microbiology make your head spin? The authors make the subject accessible and fun, to help you grasp life at the cellular level. Whether you need to score big at exam time, or just want to satisfy your curiosity, this guide will help you discover the main types of microorganisms and the benefits of their microbial communities.
pt. VII. The part of tens -- 20. Ten (or so) diseases caused by microbes -- Ebola -- Anthrax -- Influenza -- Tuberculosis -- HIV -- Cholera -- Smallpox -- Primary amoebic menigoencephalitis -- The unknown -- 21. Ten great uses for microbes -- Making delicious foods -- Growing legumes -- Brewing beer, liquor, and wine -- Killing insect pests -- Treating sewage -- Contributing to medicine -- Setting up your aquarium -- Making and breaking down biodegradable plastics -- Turning over compostable waste -- Maintaining a balance -- 22. Ten great uses for microbiology -- Medical care -- Dental care -- Veterinary care -- Monitoring the environment -- Making plants happy -- Keeping fish swimming strong -- Producing food, wine, and beer -- Science hacking -- Looking for microbes in clean rooms -- Producing pharmaceuticals.
Keywords: Microbiological Phenomena; Communicable diseases -- Microbiology; Immunity